2008
DOI: 10.3748/wjg.14.3464
|View full text |Cite
|
Sign up to set email alerts
|

Liver cell transplantation for Crigler-Najjar syndrome type I: Update and perspectives

Abstract: Liver cell transplantation is an attractive technique to treat liver-based inborn errors of metabolism. The feasibility and efficacy of the procedure has been demonstrated, leading to medium term partial metabolic control of various diseases. Crigler-Najjar is the paradigm of such diseases in that the host liver is lacking one function with an otherwise normal parenchyma. The patient is at permanent risk for irreversible brain damage. The goal of liver cell transplantation is to reduce serum bilirubin levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 68 publications
2
60
0
Order By: Relevance
“…Parental noncompliance for prescribed phototherapy coupled with inadequate immunosuppression ultimately led to OLT (Ambrosino et al 2005). Lysy et al (2008) reported HTx in two pediatric CN I patients. Patient 1 received 6.1 × 10 9 hepatocytes at age 9 years using a series of 18 infusions (delivered via catheter to the jejunal vein) over a 5 month timeframe.…”
Section: Htx For Inherited Metabolic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental noncompliance for prescribed phototherapy coupled with inadequate immunosuppression ultimately led to OLT (Ambrosino et al 2005). Lysy et al (2008) reported HTx in two pediatric CN I patients. Patient 1 received 6.1 × 10 9 hepatocytes at age 9 years using a series of 18 infusions (delivered via catheter to the jejunal vein) over a 5 month timeframe.…”
Section: Htx For Inherited Metabolic Diseasesmentioning
confidence: 99%
“…Serum bilirubin levels decreased approximately 30% in comparison to pre-transplant levels, but spiked 6 months post-transplant and he progressed clinically to OLT. The second patient (a female) received 14 infusions of 2.6 × 10 9 hepatocytes at 1 year of age (Lysy et al 2008). The total hepatic mass transplanted was ~9%; serum bilirubin fell approximately 25% and skin jaundice rapidly improved.…”
Section: Htx For Inherited Metabolic Diseasesmentioning
confidence: 99%
“…These therapies temporarily decreased bilirubin levels. As patients were hospitalized for only several days, some more effective therapies, such as liver transplantation and hepatocyte transplantation (Lucey et al, 2000;Lysy et al, 2008), were not applied. In the near future, gene therapy may be a prospective therapeutic method (Bortolussi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the risk of complications, a mortality up to 10 % in the first year [70], the burden of lifelong immunosuppressive therapy and the lack of sufficient liver donors, the development of new alternative curative therapies is warranted. Since only about 10 % of normal UGT1A1 activity is sufficient to reduce serum bilirubin levels to levels below those causing brain damage, several patients have been treated with transplantation of donor hepatocytes [71][72][73]. In most patients, a partial reduction of serum bilirubin levels was seen.…”
Section: Current Treatment For Crigler-najjar Syndromementioning
confidence: 96%